2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26629
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Competitions as Pathways to Development of Professional Engineering Skills

Abstract: In this paper we present preliminary findings from a research project aimed at identifying learning outcomes in informal environments. We focused on engineering competitions which have gained momentum across a range of engineering disciplines. Increasingly, students are participating in design competitions that range anywhere from multi-year activities such as Concrete Canoe and Formula SAE to short term activities such as one day competitions or Hack-a-thons. Although competitions are becoming popular, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The results are consistent with previous research [2], [7], [10][11] about the impact of extra-/cocurricular activities on students' academic achievements and their confidence in their capability to perform an activity -self-efficacy-. Suggesting that engineering students' engagement in engineering extra-/co-curricular activities enhances academic skills reinforcing and strengthening the knowledge they gain through engineering coursework.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results are consistent with previous research [2], [7], [10][11] about the impact of extra-/cocurricular activities on students' academic achievements and their confidence in their capability to perform an activity -self-efficacy-. Suggesting that engineering students' engagement in engineering extra-/co-curricular activities enhances academic skills reinforcing and strengthening the knowledge they gain through engineering coursework.…”
Section: Discussionsupporting
confidence: 92%
“…As competition teams gain popularity, some researchers are seeking to understand the impact of including informal learning experiences similar to competition teams on a student's academic and professional development. For example, Bland et al performed a qualitative study examining students' experiences developing professional skills through participation in an engineering competition team [10]. They conducted a series of interviews with students on the team in which they learned that with respect to professional skills, students most frequently discussed their professional and ethical responsibility as engineers but also often mentioned the need for self-management (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, middle school students indicated that instructional practices in gifted programs supported and promoted self-regulatory processes such as time management and task management including setting goals and self-monitoring. These aspects of discussions of self-regulation are similar to informal learning opportunities such as engineering competitions with the program presenting opportunities to learn or reinforce the time management and task management skills of self-regulated learning (Bland, Kusano, & Johri, 2016). Overall, both elementary and middle school students-especially middle school students-appreciated teachers' efforts to teach them to become responsible, independent, self-regulated learners.…”
Section: Developmental Differencesmentioning
confidence: 99%
“…Previous research has focused on professional skills that stem directly from ABET criterion. For instance, studies have used the ABET criteria as a guide to see which outcomes students are practicing on project teams (Bland et al, 2016;Koehn, 2006). While others investigate particular skills such as leadership and ethics that are part of ABET (Burt et al, 2011;Wolfinbarger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%